ЗАСТОСУВАННЯ МЕТОДІВ ЛОГІСТИКИ В ПСИХОЛОГІЇ РОЗВИТКУ ДИТИНИ - Піддубна Н. М.; Коваленко Ю. Ю. (International Journal of Innovative Technologies in Social Science, 2019)
In work the possibility of applying a logistic approach in educational psychology is considered. Justification of the choice of preschool age child development is a very relevant task and the subject of study of many scientists - psychologists. The work contains proposition to consider coming information as the streaming process and, accordingly, to rationalize the development system by optimizing the flow of knowledge. To justify the possible direction of child's development, it is proposed to use the method of analytical hierarchies, which allows to make decisions for multicriterial tasks. Experimental calculations based on the initial data, obtained by the observation method, allowed to make recommendations on further direction of the “chosen” knowledge flow for development of the child in accordance with his individual abilities.